2013
DOI: 10.1159/000345259
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Active Contact Positions with the Electrophysiological and Anatomical Subdivisions of the Subthalamic Nucleus in Deep Brain Stimulation

Abstract: Background: The most effective contacts in subthalamic nucleus (STN) deep brain stimulation are reported to be dorsolateral, and suppression of synchronized oscillatory activity might be a mechanism of action. Objectives: To analyze the optimal contact position in regard to the anatomical and electrophysiological position and to determine whether oscillatory and bursty activity is more frequent around the active contact. Methods: In 21 patients, the clinically most effective contacts were analyzed according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 54 publications
(36 reference statements)
1
25
1
Order By: Relevance
“…While numerous studies have suggested that the stimulation site correlated with the best clinical results in PD patients is located in the superior and lateral part of the STN [27,28,29,30], PSA DBS in PD patients have also suggested a positive effect on rigidity and bradykinesia. These findings should, however, be taken cautiously since the experience with PSA DBS is limited.…”
Section: Discussionmentioning
confidence: 99%
“…While numerous studies have suggested that the stimulation site correlated with the best clinical results in PD patients is located in the superior and lateral part of the STN [27,28,29,30], PSA DBS in PD patients have also suggested a positive effect on rigidity and bradykinesia. These findings should, however, be taken cautiously since the experience with PSA DBS is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies indicate that there is a distinct relationship between specific electrode location within the STN and the corresponding therapeutic outcome (35, 36). Our finding of predominant activation in motor networks with associated limbic activation might be attributed to current spread into ventral STN and nearby associated regions (37, 38).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies incorporating MER reported even more detailed somatotopic organization, and revealed that arm-related STN cells were located laterally and at the rostral and caudal poles, whereas leg-related cells were located medially and centrally (Rodriguez-Oroz et al, 2001; Theodosopoulos et al, 2003; Romanelli et al, 2004). Clinically, most effective DBS treatment is associated with stimulation of the dorsal STN region (Godinho et al, 2006; Weise et al, 2013). Neural activity of the anterior-medial area of the STN can be correlated with checking behavior in the STN of patients with OCD (Burbaud et al, 2013).…”
Section: Discussionmentioning
confidence: 99%